Pengaruh Emotional Marketing pada Iklan Online terhadap Purchase Intention melalui Brand Awareness (Studi Kasus: Marketplace Shopee Indonesia) - Henni, Carmel Novella; Sondari, Mery Citra (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Digitalization has given Indonesia the opportunity to become the sixth country with the largest number of start-ups in the world. However, only 10% of start-ups survive in Indonesia due to failed marketing. Therefore, this research is presented to analyze emotional marketing as a marketing strategy that can be considered to overcome this problem, where emotions are believed by many experts to be the trigger for 95% of purchase intentions in the Indonesian e-commerce industry. The data collected came from 233 samples who had seen Shopee advertisements, which were then processed using PLS SEM with Smartpls 4.0 software. Based on this research, it was found that emotional marketing has a significant effect on purchase intention, emotional marketing has a significant effect on brand awareness, brand awareness has a significant effect on purchase intention, and emotional marketing has a significant effect on purchase intention through brand awareness. This research contributes to updating knowledge related to emotional marketing in the Indonesian e-commerce industry and can be used by start-ups in their efforts to implement emotional marketing strategies in their marketing activities.